2003
DOI: 10.1074/jbc.m303913200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor α Regulates Expression of the Orphan Receptor Small Heterodimer Partner

Abstract: Hormonal status can influence diverse metabolic pathways. Small heterodimer partner (SHP) is an orphan nuclear receptor that can modulate the activity of several transcription factors. Estrogens are here shown to directly induce expression of the SHP in the mouse and rat liver and in human HepG2 cells. SHP is rapidly induced within 2 h following treatment of mice with ethynylestradiol (EE) or the estrogen receptor ␣ (ER␣)-selective compound propyl pyrazole triol (PPT). SHP induction by these estrogens is compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 72 publications
3
47
0
Order By: Relevance
“…4a). Consistent with these observations, we also evaluated the transcriptional regulations of previously reported estrogenresponsive genes, including SHP and LRH-1 [22,23]. Upregulations of these genes were observed in FOXP1-overexpressing MCF-7 cells treated with 100 nM of estrogen (Fig.…”
Section: Foxp1 Promotes Er-mediated Transcriptionsupporting
confidence: 73%
“…4a). Consistent with these observations, we also evaluated the transcriptional regulations of previously reported estrogenresponsive genes, including SHP and LRH-1 [22,23]. Upregulations of these genes were observed in FOXP1-overexpressing MCF-7 cells treated with 100 nM of estrogen (Fig.…”
Section: Foxp1 Promotes Er-mediated Transcriptionsupporting
confidence: 73%
“…PPARγ has been shown to inhibit the expression of the aromatase gene, a key enzyme in estrogen biosynthesis (25). Conversely, a recent study demonstrated that estrogens can induce expression of the small heterodimer partner, a nuclear receptor that can modulate the activity of several transcription factors, including PPARα and PPARγ (26). Hence, hormonal factors may potentially modulate the action of PPARG variants and underlie these gender-specific associations.…”
Section: Discussionmentioning
confidence: 99%
“…SHP activation by FXR ligands in hepatocytes leads to the repression of cholesterol 7␣-hydroxylase expression, the rate-limiting enzyme in the neutral pathway that leads to bile acid production from cholesterol (33). SHP is also a known target for other nuclear receptors, including the estrogen receptors and PPAR␥ (65,66), and is essential in the regulation of the expression/activity of hepatocyte NF4 and retinoid X receptor (66). A body of evidence suggest that SHP represents an important mediator of FXR activity and acts as a corepressor of FXR target genes in different physiological contexts (33,36,46,47).…”
Section: Discussionmentioning
confidence: 99%